Long-term safety of aromatase inhibitors in the treatment of breast cancer - Jean-Marc A Nabholtz (Dove Medical Press, 2008)
Jean-Marc A NabholtzBreast Cancer Research Institute La Prandie, Valojoulx, FranceAbstract: Following promising data for metastatic breast cancer in terms of efficacy and safety profile, third-generation aromatase inhibitors (AI), anastrozole, letrozole, and exemestane, underwent a full development in early setting. If recent results consistently show the superiority of these agents over tamoxifen, the therapeutic strategies of AIs in adjuvant setting are still debated. Beyond the choice of clinical strategy, the long duration of exposure to AI in adjuvant setting required a full determination of the long-term toxicity profile of these agents. While all three AIs have either favorable (decreased incidence of hot flashes, gynecologic and thromboembolic side-effects) or unfavorable (skeletal complications, arthralgia, musculoskeletal pain, sexual dysfunction) class adverse events, some variability between AIs has been reported in side-effects as well as gastrointestinal, urogenital, neurologic, and visual disturbances, confirming the lack of interchangeability between the three AIs. The overall therapeutic index of AIs appears today superior to that of tamoxifen with proven improved efficacy and better toxicity profile. This review will explore the results from the available adjuvant AIs trials with a particular emphasis on safety profiles, quality of life, and therapeutic index, helping to define the present role of AIs in the adjuvant management of postmenopausal patients with breast cancer.Keywords: breast cancer, aromatase inhibitors, adjuvant, safety profile